Comparison of spatially and temporally resolved energy system models with a focus on Germany's future power supply. (1st December 2019) - Gils, Hans Christian; Pregger, Thomas; Flachsbarth, Franziska; Jentsch, Mareike; Dierstein, Constantin
Highlights: New approach of systematic model comparison with harmonized input data. Lessons learnt from a model experiment with four high resolution power system models. Identification of impacts of different technology modelling approaches on the results. Detailed results of three scenarios for the German power supply system in 2050. New quantitative results for the future use of different load balancing options. Abstract: Energy system models usually have different data structures and mathematical approaches and therefore arrive at different results that are mostly not directly comparable. This aspect has a high relevance with regard to model-based scenario analyses for future energy systems. In addition, the variable nature of wind and solar power and their intended further expansion raise new questions of increasing complexity, such as the future role of different load balancing options. In this context the present contribution adds a new approach of systematic model comparison considering energy system models with a regional and hourly resolution. We carried out a model experiment under conditions that allow for a transparent comparison of modelling approaches and thus link differences in the results with properties of the models. The analysis includes different scenarios for a mostly renewable power system with sector coupling for Germany. The quantitative results reveal the impact of different technology modelling approaches when using input data that are as identical as possible. In addition the analysis provides new conclusions for the possible role of different load balancing options and the robustness of the underlying modelling. Furthermore, it provides insight into the lessons learnt from designing an energy system model experiment.